Immunosuppressant Therapies in COVID-19: Is the TNF Axis an Alternative? - Yadira Palacios; Leslie Chavez-Galan (MDPI AG, 2022)
The study of cytokine storm in COVID-19 has been having different edges in accordance with the knowledge of the disease. Various cytokines have been the focus, especially to define specific treatments; however, there are no conclusive results that fully support any of the options proposed for emergency treatment. One of the cytokines that requires a more exhaustive review is the tumor necrosis factor (TNF) and its receptors (TNFRs) as increased values of soluble formats for both TNFR1 and TNFR2 have been identified. TNF is a versatile cytokine with different impacts at the cellular level depending on the action form (transmembrane or soluble) and the receptor to which it is associated. In that sense, the triggered mechanisms can be diversified. Furthermore, there is the possibility of the joint action provided by synergism between one or more cytokines with TNF, where the detonation of combined cellular processes has been suggested. This review aims to discuss some roles of TNF and its receptors in the pro-inflammatory stage of COVID-19, understand its ways of action, and let to reposition this cytokine or some of its receptors as therapeutic targets.